Ancient Schwannoma in Proximity to the Median Nerve in the Midarm of an Elderly Woman - Milind A. Deshmukh; Vitaladevuni B. Shivkumar; Niloy R. Datta (Journal of Radiation and Cancer Research, 2025)
Ancient schwannomas (ASs) are a rare type of schwannomas which arise from the Schwann cells. They are characterized by benign nature and long-standing course. Their histopathological hallmark is hemorrhagic and degenerative changes with nuclear atypia. They can be misdiagnosed as malignant tumors but are differentiated by absence of mitotic activity. The median nerve in the arm is rarely involved. Even rarer is the appearance of ASs away from the main median nerve. We describe a case of AS present in proximity to the median nerve in the midarm of an elderly woman. The tumor grew relatively faster over 1.5 years and the patient presented with pain and swelling in the medial side of the right midarm. Following imaging and histopathological examination (HPE), definitive diagnosis was reached. Surgical excision was done performed and further HPE confirmed AS. The patient was further subjected to external beam radiotherapy (RT; 50 Gy over 5 weeks in 25 fractions) to prevent recurrence. RT was well tolerated, and at 2 months of follow-up, there was absence of any radiological sign of recurrence. The differential diagnoses of AS include sarcomas and tumors of neural origin. History, clinical presentation, imaging, and histopathology findings are critical in arriving at the diagnosis of AS.